Optional Vaccines for Better Immunization : Awareness among Mothers - Punarva, M.H. (Journal of Health and Allied Sciences NU, 2016)
Effectiveness of structured teaching programme on knowledge of optional vaccines among mothers of under five children in selected rural areas. The Sample include 30 mothers of under five children.Research approach was quantitative - evaluative approach anddesign used was quasi experimental pretestposttest design.In the first phase, researcher assessed pretest knowledge and health teaching was given to selected mothers with the duration of 45 minutes. The posttest knowledge was assessed over a period of 7 days after the intervention. The community participation has found to be effective with a Paired t valve (P<0.001) shows significance which indicates community participation was effective in terms of knowledge pain.
Keywords: optional vaccines; knowledge